Small Firm Lending Contracts: Do Banks Differentiate between Firms? - Marc Cowling; Roger Sugden (Journal of Small Business Finance, 1995)
This paper examines the role of interest rates and securities within the context of the small firm - bank lending relationship and questions whether banks alter their lending conditions on the basis of specific firm characteristics and the nature of the borrowing undertaken. The results suggest that the imposition of full collateralization reduces the role of interest rates considerably, although there is evidence of banks exercising their market power in more costly lending of the smallest of firms.
Keywords: G21; L25; G32; 650; Small Firms; Small Business; Lending Contracts